Study of Influence of Social and Economic Variables on Academic Performance of Students Preparing for Joint Engineering Entrance Exam in Delhi - Prof. Loknath Mishra, Vanita Mann, Dr. G N Tiwari (International Journal of Modern Agriculture, 2021)
Aims: To study the demographic profile of the JEE competitive exam aspirants preparing in coaching institutes as well as those who prepare by themselves for the exam in Delhi .Second , to assess the stress levels of the JEE competitive exam aspirants preparing in coaching institutes as well as those who prepare by themselves for the exam. Third, to study the influence of social and economic variables on academic performance of these competitive exam aspirants . Methods: In the descriptive study, cross –sectional study design was used. The population of the study was aspirant students preparing in coaching institutes as well as those who prepare by themselves for JEE competitive exam in Delhi. The sample consisted of 300 adolescents( 150 each attending engineering coaching institute and those do not attend coaching institutes). Non random sampling method was used to select the subjects of the study. A well- structured open ended questionnaire was self- administered to the students and data (responses) was collected. A total of 300 adolescents filled the questionnaire. The data was analysed using frequency and percentage analysis of each item was done. Findings: The findings of the study indicated that among the stressors- academic, parental and personal stressors affected the student’s performance and thus increase stress levels . Also among the social and economic variables parents educational levels, parental income ,moral support provided by both mother and father , social and economic standard of both mother and father, family size ,family composition and locality of the aspirant students influence the success and achievement of the engineering competitive exam aspirants preparing in coaching institutes as well as those who prepare by themselves.